Simplicity and the form of grammars - Chomsky, Noam (Journal of Language Modelling, 2021)
The goal of theory construction is explanation: for language, theory for particular languages (grammar) and for the faculty of language FoL (the innate endowment for language acquisition). A primitive notion of simplicity of grammars is number of symbols, but this is too crude. An improved measure distinguishes grammars that capture genuine properties of language from those that do not. The theory of FoL must meet the empirical conditions of learnability (under extreme poverty of stimulus), and evolvability (given the limited but not insignificant evidence available). Recent work provides promising insights into how these twin conditions may be satisfied.